2017
DOI: 10.1037/pst0000085
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to psychotherapy termination.

Abstract: Collaboration has been recognized as an important relationship variable in psychotherapy that is linked to client treatment outcomes. Although many therapists seek to build a collaborative working relationship with their clients when making treatment decisions, collaboration is also an important technique that can be used to help clients plan for a successful termination. Collaborative termination strategies can first be used in the initial session in order to address clients' termination expectations. Strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Therapeutic work was tailored to the needs of adolescents and incorporated the challenges they faced in their everyday life. The quality of the clients’ participation throughout the phases of therapy may help clients take ownership of their gains, equalize the therapeutic relationship and prepare clients for their transition away from psychotherapy, supporting findings from previous studies [ 27 , 85 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therapeutic work was tailored to the needs of adolescents and incorporated the challenges they faced in their everyday life. The quality of the clients’ participation throughout the phases of therapy may help clients take ownership of their gains, equalize the therapeutic relationship and prepare clients for their transition away from psychotherapy, supporting findings from previous studies [ 27 , 85 ].…”
Section: Discussionsupporting
confidence: 80%
“…Their experiences during therapy had made them stronger, and they both had established healthier relationships with family and friends. Rethinking how participants in dyads label and conceptualize helpful aspects during the final phases of treatment may help clients to engage in dynamic work as well as healthy and helpful cognitions following treatment, supporting previous findings [ 17 , 76 , 85 , 86 ].…”
Section: Discussionsupporting
confidence: 78%
“…Theoretical discussions and studies of psychotherapists' self-reports have identified such tasks in the final phase of the therapeutic work: solidifying gains and improvements, making the client feel praised and helped, shifting the focus of talk to discussing therapeutic experience and change, framing personal development as invariably unfinished and collaboratively developing a future plan for the client's growth (Fragkiadaki and Strauss, 2012;Goode et al, 2017;Hill, 2005;Maples and Walker, 2014;Norcross et al, 2017). Remarkably, reports of experienced psychotherapists revealed commonality in termination behaviour across theoretical orientations and individual practitioners (Norcross et al, 2017).…”
Section: Closure and Therapeutic Goalsmentioning
confidence: 99%
“…Most prominently, psychoanalytic and existential approaches, with their focus on separation, loss and death, view treatment termination as a potentially powerful therapeutic experience and unique opportunity for growth. Although therapists and patients can use collaborative strategies in preparing for psychotherapy termination, setting treatment goals and addressing expectations throughout the treatment (Goode et al ., ), the termination phase itself can be particularly therapeutic. The termination phase may, for example, allow for consolidation of therapeutic work, with patient and therapist sharing the joy, pride and pleasure of the accomplishments achieved (Roe et al ., ), as well as allow for a unique opportunity to work through issues of separation and loss (Zilberstein, ).…”
mentioning
confidence: 99%
“…collaborative strategies in preparing for psychotherapy termination, setting treatment goals and addressing expectations throughout the treatment (Goode et al, 2017), the termination phase itself can be particularly therapeutic. The termination phase may, for example, allow for consolidation of therapeutic work, with patient and therapist sharing the joy, pride and pleasure of the accomplishments achieved (Roe et al, 2006), as well as allow for a unique opportunity to work through issues of separation and loss (Zilberstein, 2008).…”
mentioning
confidence: 99%